An innovative option contract for allocating water in Inter-Basin Transfers: the case of the Tagus-Segura Transfer in Spain - Rey, Dolores; Garrido, Alberto; Shafiee, Mahmood (Springer, 2015)
The Tagus-Segura Transfer (TST), the largest water infrastructure in Spain, connects the Tagus basin’s headwaters and the Segura basin, one of the most water-stressed areas in Europe. The need to increase the minimum environmental flows in the Tagus River and to meet new urban demands has lead to the redefinition of the TST’s management rules, what will cause a reduction of transferable volumes to the Segura basin. After evaluating the effects of this change in the whole Tagus-Segura system, focusing on the availability of irrigation water in the Segura, the environmental flows in the Tagus and the economic impacts on both basins; we propose an innovative two-tranche option contract that could reduce the negative impacts of the modification of the Transfer’s management rule, and represents an institutional innovation with respect to previous inter-basin water trading. We evaluate this contract with respect to spot and non-market scenarios. Results show that the proposed contract would reduce the impact of a change in the transfer’s management rule on water availability in the recipient area.
Keywords: Option contract; Supply risks; Tagus-Segura Transfer; Water markets